For love of country : leave the Democrat Party behind - Gabbard, Tulsi (Regnery, an imprint of Skyhorse Publishing, Inc., 2024)
Tulsi Gabbard was the rising star of the Democrat Party. But the growing wokeness, fomenting racism, and intolerance were more than she could stomach, and she left. This is her story and a call to action to Americans who love our country and cherish peace and freedom.